Diagnostic accuracy and added value of dynamic chest radiography in detecting pulmonary embolism: A retrospective study - Yamasaki, Yuzo; Hosokawa, Kazuya; Kamitani, Takeshi; Abe, Kohtaro; Sagiyama, Koji; Hino, Takuya; Ikeda, Megumi; Nishimura, Shunsuke; Toyoda, Hiroyuki; Moriyama, Shohei; Kawakubo, Masateru; Matsutani, Noritsugu; et al. (European journal of radiology Open, 2024)
This study aimed to assess the diagnostic performance of dynamic chest radiography (DCR) and investigate its added value to chest radiography (CR) in detecting pulmonary embolism (PE). Of 775 patients who underwent CR and DCR in our hospital between June 2020 and August 2022, individuals who also underwent contrast-enhanced CT (CECT) of the chest within 72 h were included in this study. PE or non-PE diagnosis was confirmed by CECT and the subsequent clinical course. The enrolled patients were randomized into two groups. Six observers, including two thoracic radiologists, two cardiologists, and two radiology residents, interpreted each chest radiograph with and without DCR using a crossover design with a washout period. Diagnostic performance was compared between CR with and without DCR in the standing and supine positions. Sixty patients (15 PE, 45 non-PE) were retrospectively enrolled. The addition of DCR to CR significantly improved the sensitivity, specificity, accuracy, and area under the curve (AUC) in the standing (35.6–70.0 % [P < 0.0001], 84.8–93.3 % [P = 0.0010], 72.5–87.5 % [P < 0.0001], and 0.66–0.85 [P < 0.0001], respectively) and supine (33.3–65.6 % [P < 0.0001], 78.5–92.2 % [P < 0.0001], 67.2–85.6 % [P < 0.0001], and 0.62–0.80 [P = 0.0002], respectively) positions for PE detection. No significant differences were found between the AUC values of DCR with CR in the standing and supine positions (P = 0.11) or among radiologists, cardiologists, and radiology residents (P = 0.14–0.68). Incorporating DCR with CR demonstrated moderate sensitivity, high specificity, and high accuracy in detecting PE, all of which were significantly higher than those achieved with CR alone, regardless of scan position, observer expertise, or experience. [Display omitted] A)Images of chest radiography (left) and dynamic chest radiography (right) in a patient with acute pulmonary embolism. Large wedge-shaped perfusion defects are observed in bilateral lungs (arrows).B)Images of chest radiography (left) and dynamic chest radiography (right) in a patient without pulmonary embolism.C)Receiver operating characteristic curves for CR without DCR in the standing position, CR without DCR in the supine position, CR with DCR in the standing position, and CR with DCR in the supine position. Significant differences are observed between CR without DCR and CR with DCR both in standing and supine positions. CR, chest radiography; DCR, dynamic chest radiography. •DCR showed moderate sensitivity, high specificity, and high accuracy in detecting PE.•The addition of DCR increased the diagnostic ability of observers for PE detection.•These findings highlight the potential of DCR as a valuable diagnostic tool for PE.